John : a new covenant commentary - Kanagaraj, Jey J. (Cambridge : Lutterworth Press, 2013)
In this commentary Kanagaraj examines how John projects the church as God's ""new covenant community"", which is characterized by two virtues: love and obedience. Impossible to exhibit under the old covenant based on Moses' Law, these qualities became possible by the initiative grace and faithfulness of God revealed in Jesus and demonstrated by the power of the Spirit. God's new community is an inclusive and progressive community because its witness to Jesus in a world that hates and persecutes it has the power to bring in all people so that they may become one ock under one shepherd. Kanagara.
John 10: The Impact of Jesus on His Community and on OthersJohn 11: Lazarus' Resurrection and Its Implications; John 12: The Final Journey of Jesus to Jerusalem; John 13: Jesus' Last Supper with His Disciples; John 14: Jesus' Pastoral Speech I; John 15: Jesus' Pastoral Speech II; John 16: Jesus' Pastoral Speech III; John 17: Pastoral Prayer of Jesus; John 18: Arrest and Trials Faced by Jesus; John 19: The Supreme Revelation of God's Glory; John 20: Visions of the Risen Jesus; John 21: Epilogue ; Bibliography; Back cover.
Includes bibliographical references.
Online resource; title from PDF title page (ebrary, viewed October 14, 2013).
Master record variable field(s) change: 072
Keywords: Bible. -- Commentaries; Bible; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts; RELIGION -- Biblical Studies -- New Testament; RELIGION / Christian Theology / History; Electronic books; Commentaries